Effectiveness of Edugame Integration in Problem Based Learning: Impact Analysis on Students' Critical Thinking and Motivation - Tiawanti; M. Zainal Arifin; Deddy Sofyan S (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2026)
Several studies have shown that the low score of Indonesia's PISA in 2022 is due to weak 21st-century skills competencies, such as critical thinking skills. The implementation of learning models and media has not been able to facilitate students' critical thinking. Students only listen, read books, and do recall exercises. This study aims to provide alternative solutions for implementing a problem-based learning model assisted by edugames to improve critical thinking skills and learning motivation, using a quasi-experimental method with a Pretest and Posttest Control-Group. The study subjects involved 40 fifth-grade elementary school students, divided into a control class using problem-based learning without edugames and an experimental class using problembased learning assisted by edugames. Analysis of critical thinking skills using the N-Gain test showed that the control class obtained a score of 0.44 in the moderate category and the experimental class 0.71 in the high category. Student learning motivation was indicated by the questionnaire results, which were 93.4% in the very strong criteria. The t-test results illustrated a significant difference between the control and experimental classes. This study concluded that problem-based learning assisted by edugames is effective in improving students' critical thinking skills and learning motivation. Abstrak: Beberapa kajian faktor rendahnya skor PISA Indonesia tahun 2022 disebabkan lemahnya kompetensi keterampilan.abad ke-21, seperti keterampilan berpikir kritis. Implementasi model dan media pembelajaran belum mampu memfasilitasi siswa berpikir kritis. Siswa hanya menyimak, membaca buku dan mengerjakan soal latihan bersifat recall. Penelitian ini bertujuan menghasilkan solusi alternatif implementasi model pembelajaran berbasis masalah berbantuan edugame untuk meningkatkan keterampilan berpikir kritis dan motivasi belajar, dengan metode kuasi eksperimen desain rancangan Pretest and Posttest Control-Group Design. Subyek penelitian melibatkan 40 siswa kelas 5 Sekolah Dasar, terbagi kelas kontrol menggunakan pembelajaran berbasis masalah tanpa edugame dan kelas eksperimen menggunakan pembelajaran berbasis masalah berbantuan edugame. Analisis keterampilan berpikir kritis menggunkan uji N-Gain kelas kontrol memperoleh 0,44 kategori sedang dan kelas eksperimen 0,71 kategori tinggi. Motivasi belajar siswa ditunjukkan dengan hasil angket yaitu 93,4% kriteria sangat kuat. Hasil uji-t menggambarkan perbedaan signifikan kelas kontrol dan eksperimen. Penelitian ini menyimpulkan bahwa pembelajaran berbasis masalah berbantuan edugame efektif meningkatkan keterampilan berpikir kritis dan motivasi belajar siswa.